Ukuran Perusahaan dan Jenis Industri: Determinan Audit Delay Emiten LQ45 di BEI Tahun 2021-2023 - Anastasya Utami; Tony Sudirgo (Cerdika: Jurnal Ilmiah Indonesia, 2025)
The purpose of this study is to examine the impact of company size and industry type on audit delay. The research utilizes secondary data from the audited financial statements of LQ45 issuers published by the Indonesia Stock Exchange (IDX) between 2018-2023. A saturated sampling technique was employed, which involved using the entire population. Data analysis was conducted using SPSS 27. The findings indicate that company size does not have a significant effect on audit delay; however, industry type does have a significant effect. Future researchers are encouraged to investigate additional independent variabeliables that may influence audit delay and to broaden the scope of their research objects and timeframes.